Osteology and systematics of Uberabatitan ribeiroi (Dinosauria; Sauropoda): a Late Cretaceous titanosaur from Minas Gerais, Brazil - Silva, Julian C. G. Junior; Marinho, Thiago S.; Martinelli, Agustín G.; Langer, Max C. (Zootaxa, 2019)
Uberabatitan ribeiroi is a Late Cretaceous titanosaur (Dinosauria, Sauropoda) from southeastern Brazil. Here we provide a detailed revision of all its available specimens, including new elements from the type-locality. One new autopomorphy is added to diagnosis of the taxon: astragalus with a well-developed anteroposterior crest that mediodistally delimits the tibial articulation. Linear regressions were conducted in an attempt to circumscribe specimens within the type-series, revealing that it is composed of several individuals, with inferred total body lengths varying from 7 to 26 meters. Phylogenetic analyses including U. ribeiroi show that the Brazilian taxon corresponds to a non-saltasaurid lithostrotian titanosaur.